AB0586 104-weeks assessments of clinical and structural remission in rheumatoid arthritis patients with tocilizumab from the reaction study. (23rd January 2014) - Tanaka, Y.; Takeuchi, T.; Amano, K.; Sato, E.; Nawata, M.; Nagasawa, H.; Hoshi, D.; Saito, K.; Fukuyo, S.; Hanami, K.; Kameda, H.; Kurasawa, T.; et al.
Abstract : Background: Tocilizumab (TCZ) showed highly efficacious in rheumatoid arthritis (RA) in the clinical trials, although there is little evidence in daily clinical practice. We have already reported the effects of TCZ for 52 weeks when used in clinical practice (REACTION Study). Objectives: We investigate effects of TCZ on disease activity and joint destruction in patients with RA when used in clinical practice (REACTION Study) for 104 weeks. We also assess the efficacy of TCZ in clinical and radiographical changes in patients switched from TNF inhibitors to TCZ. Methods: Patients received 8 mg/kg of TCZ every 4 weeks. DAS28-ESR, CDAI, HAQ, and modified Total Sharp Score (mTSS) were evaluated for 104 weeks. We also investigated clinical and structural effects of switching from TNF inhibitors to TCZ in patients for whom x-rays were taken during TNF inhibitor treatment. Results: This study enrolled 229 patients in total. At baseline, mean age was 58.8±13.7 years, mean disease duration was 12.2±10.4 years, and 64.2% of the patients had been treated previously with TNF inhibitors. The DAS28-ESR remission (DAS28 <2.6) rate after 104 weeks was 52.2% (LOCF) and 39.5% (non-responder imputation [NRI]), and the CDAI remission (CDAI ≤2.8) rate was 26.0% (LOCF) and 20.7% (NRI). The proportion of patients achieving structural remission (delta mTSS ≤0.5) was 52.9%. The CDAI score at 52 weeks was identified by multivariate analysis as a predictive factor for structural remission at 104 weeks (p=0.022). The cutoff value from the ROC curve revealed that prevention of joint destruction at 104 weeks was found in 73.1% of patients with CDAI ≤3.1 at 52 weeks (p=0.034). We also investigated the effects at 52 weeks before and after TCZ treatment in the 38 patients switched from TNF inhibitors to TCZ. The results revealed that the DAS28-ESR remission rate and the CDAI remission rate were both 0% during TNF inhibitor therapy, but were 50.0% and 18.9%, respectively, 52 weeks after TCZ treatment initiation (p<0.001). The mean delta mTSS during TNF inhibitor treatment was 3.55, but improved to 1.37 after the switch to TCZ (p=0.041). Conclusions: In daily clinical practice, TCZ exhibits adequate efficacy in preventing joint destruction in patients with advanced RA. The CDAI score at 52 weeks was identified by multivariate analysis as a predictive factor for structural remission at 104 weeks, indicating the significance of CDAI as the "real remission" for good outcomes in radiographic damage. Moreover, TCZ also exhibits significant inhibition for patients with inadequate response to TNF inhibitors. When it was judged that TNF inhibitors did not have adequate response, it appears to be important to switch to TCZ with different mode of action in the early stage of treatment. Disclosure of Interest: Y. Tanaka Grant/Research support from: Abbott, Astellas Pharma, Chugai Pharma, Mitsubishi-Tanabe Pharma, MSD, Pfizer, Takeda, Speakers Bureau: Abbott, Astellas Pharma, Chugai Pharma, Eisai Pharma, Mitsubishi-Tanabe Pharma, T. Takeuchi Grant/Research support from: Abbott, Bristol-Myers Squibb, Chugai Pharma, Eisai Pharma, Mitsubishi-Tanabe Pharma, Takeda Pharma, Janssen Pharma, Pfizer, K. Amano Grant/Research support from: Abbott, Astellas Pharma, Chugai Pharma, Eisai Pharma, Mitsubishi-Tanabe Pharma, E. Sato: None Declared, M. Nawata: None Declared, H. Nagasawa: None Declared, D. Hoshi: None Declared, K. Saito: None Declared, S. Fukuyo: None Declared, K. Hanami: None Declared, H. Kameda Grant/Research support from: Mitsubishi-Tanabe Pharma, Centocor, Pfizer, Takeda Pharma, Abbott, Eisai Pharma, Chugai Pharma, T. Kurasawa: None Declared, Y. Kaneko: None Declared, H. Yamanaka Grant/Research support from: Abbott, Bristol-Myers Squibb, Chugai Pharma, Eisai Pharma, Hoffmann-La Roche, Mitsubishi-Tanabe Pharma, Takeda Pharma, Pfizer